The Use of Dynamic Systems Based on Shape Memory Alloys for the Treatment of Neuromuscular Disorders. Issue 20 (2015) - Pittaccio, Simone; Garavaglia, Lorenzo; Ceriotti, Carlo; Passaretti, Francesca
Abstract: Shape Memory Alloys (SMA) are very versatile materials that display a number of unusual and interesting properties, in particular, pseudoelasticity, thermally-activated shape memory, mechanical and thermal hysteresis. All of these characteristics can be thought of as sources of inspiration in the development of dynamic systems for mechanical or mechatronic applications. This paper will focus on several results obtained in the field of Neuromuscular Rehabilitation and Neurology. The need to customise functions, to make devices lightweight, portable and suitable to be interfaced with modern diagnostic instrumentation, and a drive towards the development of technologies appropriate for home-based therapies are the reasons why employing SMA in the design of biomedical systems for the treatment of neuromuscular disorders can show all the advantages of solid-state actuation and sensing.